2022
DOI: 10.1177/02724316221105560
|View full text |Cite
|
Sign up to set email alerts
|

Types of Social Media Use and Digital Stress in Early Adolescence

Abstract: Evidence on how different types of social media use contribute to digital stress in early adolescence is lacking. In-depth interviews were conducted with 24 13–14-year-olds. Interviews were transcribed verbatim, coded and thematically analysed. Themes were generated based on digital stressors specific to passive social media use (time-wasting and digital guilt, and exposure to harmful content); private social media communication (expectations of availability and unsolicited contact by strangers); and social me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These studies have found some evidence that different types of uses have different effects on adolescent mental health [ 24 , 34 , 40 , 41 ]. Passive use of social media has been associated with social comparison, envy, and feelings of anxiety and depression compared to active use [ 24 , 40 , 42 ]. In this study, there was only an active measure of social media available, which may explain why this study did not find a significant relationship between social media use and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found some evidence that different types of uses have different effects on adolescent mental health [ 24 , 34 , 40 , 41 ]. Passive use of social media has been associated with social comparison, envy, and feelings of anxiety and depression compared to active use [ 24 , 40 , 42 ]. In this study, there was only an active measure of social media available, which may explain why this study did not find a significant relationship between social media use and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while we found significant effects of the alliance or bond and task/goal scores on comments and reactions, no aspects of the alliance predicted a greater number of posts. Relative to the subtlety of comments and reactions which are embedded within posts, it is possible that the way posts are displayed on the newsfeed amplifies visibility and perceived permanence of the material once shared with the community, stressors which may complicate or frustrate social engagement and which are unique to digital settings (Nesi et al., 2023; Winstone et al., 2023). It is currently unknown whether prosocial effects of the alliance can overcome these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Perceiving friends to view DSMT negatively was directly related to higher digital stress. When teens perceive negative injunctive norms of DSMT, they likely face a dilemma—while their friends consider DSMT disruptive, dismissive, and disrespectful, teens simultaneously sense a strong expectation for immediate digital response [ 12 , 29 , 40 ], which would be difficult to achieve without DSMT. The two expectations present a goal conflict, which has been found to be associated with higher digital stress [ 18 ] and may be an underlying mechanism for this direct path.…”
Section: Discussionmentioning
confidence: 99%
“…However, such expectation has led to an increase in demands on users' attention and responses, thereby increasing stress [ 1 ]. Many types of digital stress have been identified [ 4 , 12 ], and Steele et al’s [ 2 ] recent conceptualization of digital stress provides a useful framework to study the phenomenon. Steele et al defined digital stress as the subjective experience of having insufficient resources to cope with the stress caused by digital media in one's social and relational contexts.…”
Section: Introductionmentioning
confidence: 99%